Horan Valley Environmental Monitoring Based on its Digital Elevation Model to the 2023 Year - Jawad, Laith A. (Iraqi Journal of Science, 2024)
The ecological interaction, human, geomorphological, and climatological factors lead to basin morphometry; morphometric aspects could be used as evidence for understanding the nature of these factors in terms of active dominant factors within the basin area. Quantitative morphometric analysis based on remote sensing imageries and GIS techniques is the best way to determine these aspects. In this research, a new approach was submitted: using Google Maps to track the Horan Valley path and region that passes through, delineating the main basins in the region, and then neglecting all basins that involve the valley only. The obtained results showed that the Horan region is a four-order basin with 213 1st-order streams, 89 2nd-order streams, 35 3rd-order streams, and 84 4th-order streams, and its area is 12947 km2, the average bifurcation ratio is (1.784) indicating the flood risk in the basin during rain generally, while the sub-ratios between two successive orders refer to this risk absence in the main order streams. Dd was 0.201 km-1, revealing the area's desertification and increased soil permeability. Fs was 0.0325 stream/ km2, meaning an alluvial basin formed mainly by sediments during rainstorms. T was 0.0611 km-1, proving the region's soil's high porosity and permeability. Re was 0.289, indicating semi-rectangle basin shape and geological structures equivalence. C was 0.086, revealing that lineaments control the basin drainage pattern model, and Rf was 0.069, meaning a youth geomorphological stage and length of the water drainage period till arriving at the basin end during the rain.